P43 Patients' experiences of early post-hospitalisation pulmonary rehabilitation: A quality improvement initiative. (14th November 2013) - Fleming, SL; Jones, SE; Green, S; Clark, AL; Howe, C; Kon, SSC; Dickson, M; Godden, J; Bell, D; Haselden, BM; Man, WD-C
Abstract : Background: Early post-hospitalisation pulmonary rehabilitation (PR) following acute exacerbation of COPD (AECOPD) improves health-related quality of life, increases exercise capacity and reduces rate of hospital readmission. However, only a minority of eligible patients are referred to or receive this intervention (Jones et al Thorax 2013). We explored patient acceptability for post-AECOPD PR and the referral process through face-to-face audio- and video-taped interviews. Methods: Ten patients were interviewed using experience based co-design (EBCD) methodology: six PR "completers", one PR starter who subsequently withdrew, and 3 patients who declined PR. The films were analysed and edited to represent the common themes. A patient-staff event was held to co-design a patient information leaflet and video. Results: Overall, the patient completers were positive about their experience. They most liked: the atmosphere; the equipment; group social interaction; doing more exercise than they thought they could; learning how to manage their lung condition. They least liked: getting there; being 'shattered' afterwards; no tea and coffee break; no introductions. For patients who declined, the reasons given were: "I don't know what rehab is …… no-one has explained it"; "I was never offered rehab"; "It is too far away- I would go if transport was paid for." A recurring theme was that patients had poor recall of information provided during hospital admission. Conclusion: The findings highlighted the complexity of interactions between patient and healthcare professionals. In response to this, an information leaflet and video are being produced using the filmed interviews and feedback from the patient staff co-design event to facilitate the referral process. The best timing and delivery of patient information is currently being evaluated. Other themes were improving PR accessibility and enhancing social aspects of PR. Two new community sites were opened to provide wider coverage of the borough andrefreshments are now offered routinely during education classes. Furthermore, patients and staff are introduced to each other routinely at the beginning of PR classes. 159 referrals for post-AECOPD PR have been made in the past 18 months and patient satisfaction rates are 98%. The EBCD approach was ideal in engaging patients in the co-design of service improvements.